2020
DOI: 10.46792/fuoyejet.v5i1.456
|View full text |Cite
|
Sign up to set email alerts
|

Minimizing Interference in Ultra-Dense Femtocell Networks Using Graph-Based Frequency Reuse Technique

Abstract: This paper investigates the performance of graph colouring schemes for frequency assignment in Long-Term Evolution (LTE) networks with ultra-dense femtocells. The aim of the study is to minimize interference in such networks while ensuring efficient spectrum use for these femtocells. The three schemes investigated are the conventional greedy graph colouring algorithm, the saturation degree algorithm and our proposed graph-based theory (GBT) algorithm. The process of frequency assignment is similar in the last … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Simulation results showed that as the number of FAPs increases, the data rate decreases, because the interference between the closest FAPs increases [34] Greedy and graph-based technique (GBT) algorithms to reduce co-tier interference…”
Section: Refmentioning
confidence: 99%
See 1 more Smart Citation
“…Simulation results showed that as the number of FAPs increases, the data rate decreases, because the interference between the closest FAPs increases [34] Greedy and graph-based technique (GBT) algorithms to reduce co-tier interference…”
Section: Refmentioning
confidence: 99%
“…In addition to resource allocation methods, ref. [34] also reduced co-tier interference using greedy and graph-based technique (GBT) algorithms. Their simulation results showed that the greedy algorithm has the disadvantage of being inefficient in assigning random subbands.…”
mentioning
confidence: 99%
“…The FFR scheme makes use of a form of minimum distance constraint. In the work of Adekunle & Gbenga-Ilori (2020), authors used graph colouring frequency reuse technique for frequency assignment in communication networks with ultra-dense femtocells to minimize interference. Some other papers also used power control for coordinating spectrum sharing in D2Denabled cellular networks (Zhang et al, 2017), (Abdallah, Mansour, & Chehab, 2018), (Nguyen, & Rao, 2015).…”
Section: *Corresponding Authormentioning
confidence: 99%
“…In addition to the flat reaching 10 GB/s, 5G technology allows computing integrated with various devices to realize the Internet of Things (IoT) network scenario [2]. Based on the facts above, to prepare themselves to welcome the 5G generation, an initial study is needed to examine the application of 5G technology, especially in areas with high population density [3]. In this study, we analyzed the FemtoCell network scenario that can meet the characteristics of 5G -free cellular communication technology standards [4].…”
Section: Introductionmentioning
confidence: 99%